PENINGKATAN LITERASI KARIR DAN KESIAPAN KERJA GENERASI Z MELALUI PROGRAM MENTORING DAN SIMULASI WAWANCARA DI LINGKUNGAN SEKOLAH - Ayu Lestari; Ramla Ilham Darise; Hariani Hanapi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Generation Z faces significant challenges in preparing themselves to enter an increasingly competitive and dynamic labor market. The Community Service Program (Kuliah Kerja Nyata or KKN) of Universitas Madako Tolitoli was implemented with the aim of enhancing career literacy and work readiness among Generation Z through mentoring activities and interview simulations. This program was carried out at Pondok Pesantren Al-Ittihad DDI Soni and involved 50 participants from grades 10, 11, and 12. The methods included career literacy sessions, mentoring to support career planning, and practical interview simulations. The program was designed to equip participants with an understanding of the importance of early career preparation, communication skills, and self-confidence in facing recruitment processes. The results demonstrated an improvement in participants’ understanding of career literacy as well as their practical skills in performing interview simulations. Therefore, this program can serve as a strategic and sustainable step in supporting pesantren students to be better prepared for the labor market while contributing to the improvement of human resource quality.